El Tahuantinsuyo: Evolucin, organizacin e importancia - Benavides Lozano, Edson Lee (2020)
The Tahuantinsuyo, as an important part of the process of our vast history; culture synthesis, was one of the main empires of America; its expansion spans from Colombia, in the North, and the Maule River, in Chile, in the South, this was given thanks to a correct administrative organization that our ancestors carried out. Education being the means of disseminating knowledge, I stress the importance of knowing the evolution of this important culture. In addition to understanding its social, political and economic organization, which will strengthen the development of our students. At the end of the Late Horizon, the different regional lordships that made up the Tahuantinsuyo, due to the lack of cultural unity, favoured the Spanish invasion and were conquered and destroyed, but in spite of this, this is the most representative culture in Peruvian history and many of its customs and cultural manifestations are still in force.